2022
DOI: 10.3390/ijms23179998
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Critical Genes and Pathways in Carbon Metabolism and Ribosome Biogenesis in Poplar Fertilized with Glutamine

Abstract: Exogenous Gln as a single N source has been shown to exert similar roles to the inorganic N in poplar ‘Nanlin895′ in terms of growth performance, yet the underlying molecular mechanism remains unclear. Herein, transcriptome analyses of both shoots (L) and roots (R) of poplar ‘Nanlin895’ fertilized with Gln (G) or the inorganic N (control, C) were performed. Compared with the control, 3109 differentially expressed genes (DEGs) and 5071 DEGs were detected in the GL and GR libraries, respectively. In the shoots, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…The upregulation of β-1,3-1,4-glucanase that degrades mixed linkage glucan, a transient wall polysaccharide found in cereals such as barley, may lead to the increased energy production required for rapid seedling growth [ 40 ]. These results were consistent with several previous investigations [ 23 , 26 , 41 ], who reported that protein hydrolysate, glutamine and humic substances increased the expression of the genes related to carbohydrate metabolism, including glycolysis in various species such as maize, poplar and Arabidopsis, respectively. SnRK1, a central regulator of cellular energy homeostasis, was upregulated, which may lead to the regulation of gene expression associated with carbohydrate metabolism in compost-treated plants, thereby resulting in the control of multiple developmental processes including root cell growth and proliferation [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The upregulation of β-1,3-1,4-glucanase that degrades mixed linkage glucan, a transient wall polysaccharide found in cereals such as barley, may lead to the increased energy production required for rapid seedling growth [ 40 ]. These results were consistent with several previous investigations [ 23 , 26 , 41 ], who reported that protein hydrolysate, glutamine and humic substances increased the expression of the genes related to carbohydrate metabolism, including glycolysis in various species such as maize, poplar and Arabidopsis, respectively. SnRK1, a central regulator of cellular energy homeostasis, was upregulated, which may lead to the regulation of gene expression associated with carbohydrate metabolism in compost-treated plants, thereby resulting in the control of multiple developmental processes including root cell growth and proliferation [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…It is well known that under stressed conditions, carbohydrates can act as osmoprotectants that remove reactive oxygen species (ROS) and stabilise cellular membranes, which can protect plants from oxidative damage [ 44 ]. Under stressed conditions, several previous studies, such as those on poplar [ 41 ], Arabidopsis [ 23 ], maize [ 45 ] and potato [ 46 ], have shown that the application of biostimulants and organic amendments increases the expression of various proteins that often participate in energy and carbohydrate metabolism. These results suggest that enzymes associated with the glycolytic pathway might assist in the intensification of glycolysis to provide energy for supporting plant growth and metabolic activities under abiotic and biotic stresses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, it had been reported that OFP was involved in the fruit shape development process of pepper, and CaOVATE was found to be involved in the fruit shape process of tomato through the study of pepper varieties with different fruit shapes (Tsaballa et al, 2011). Expression pattern analysis of Citrus OFPs (CitOFPs) showed that CitOFP19 had significantly higher expression level in the ovaries of round pummelo than in those of pear-shaped pummelo (Wu et al, 2022). We also found that the CazOFP genes were up-regulated in the early stages of pepper fruit development (Dev1~Dev5) in the study.…”
Section: Expression Profiles Of Caofp Genes In Peppermentioning
confidence: 48%